Safety and efficacy of indocyanine green near-infrared fluorescent imaging-guided lymph nodes dissection during radical gastrectomy for gastric cancer: A systematic review and meta-analysis - Deng, Chun; Zhang, Zhenyu; Qi, Hengduo; Guo, Zhi; Liu, Yang; Xiao, Haimin; Li, Xiaojun (Frontiers in Oncology, 2022)
Abstract Background Indocyanine green (ICG) fluorescence imaging has been a new surgical navigation technique for gastric cancer. However, its clinical value should still be evaluated further. In this meta-analysis, we investigated the safety and efficacy of ICG near-infrared fluorescent imaging-guided lymph nodes (LNs) dissection during radical gastrectomy. Methods Studies comparing ICG fluorescence imaging with standard care in patients with gastric cancer were systematically searched from PubMed, Embase, Web of Science, and Cochrane Library through August 2021. The current meta-analysis was performed according to the preferred reporting items for systematic review and meta-analysis guidelines. A pooled analysis was performed for the available data regarding the number of LNs dissection, the number of metastatic LNs dissection, other operative outcomes, and postoperative complications. R software version 4.2.0 and Stata 16.0 software were used for the present meta-analysis. Results This analysis included 12 studies with a total of 1365 gastric cancer patients (569 in the ICG group and 796 in the non-ICG group). The number of retrieved LNs in the ICG group was significantly higher (weighted mean difference [WMD]=7.67, 95% confidence intervals [CI]: 4.73 to 10.62, P<0.05) compared to the non-ICG group with moderate heterogeneity (P<0.001, I2=70%). The number of metastatic LNs, operative time, and postoperative complications were all comparable and without significant heterogeneity. Additionally, ICG near-infrared fluorescent imaging was associated with reduced intraoperative blood loss (WMD=-10.28, 95% CI: -15.22 to -5.35, P<0.05) with low heterogeneity (P=0.07, I2 = 43%). Conclusions ICG near-infrared fluorescent imaging-guided lymphadenectomy was considered to be safe and effective in gastrectomy. ICG was used to increase the number of LNs harvested while reducing intraoperative blood loss without increasing operative time or postoperative complications. Systematic Review Registration PROSPERO database( identifier, CRD42021291863)